Potensi Minyak Atsiri Kamfer Sumatera (Dryobalanops aromatica Gaertn.) Untuk Bahan Baku Obat Herbal - Aswandi, Aswandi; Kholibrina, Cut Rizlani (Jurnal Farmasi Udayana; Spesial Issue, Desember 2020, 2020)
Camphor resin has been harvested since the seventh century from west coast of Sumatra, Indonesia. This historic oil or crystal have been collected from sumatran camphor trees ( Dryobalanops aromatica ) and utilized as fragrance, antibiotic, topical treatment for pains, and aromatherapy. The paper describes the local wisdom of camphor essential oil, phytochemical content, and potential utilization for herbal medicine. Conventionally, camphor crystals are harvested through felling and log splitting. This method produces about 1.5–2.5 kg of crystals. Extraction of camphor is also possible by making notches in standing tree trunk, as well as collecting liquid resin that exudate from wounded resin channel. The leaves biomass contains significant essential oils, especially fresh-young leaves. This volatile compound is distilled at 0.46–0.73% yield. The essential oil compounds include a-pinene, b-caryophyllene, 1.8-cineole, limonene, and p-cymene. For aromatherapy application, camphor oil has a relaxing fragrance offer relief to congested respiratory system thereby boosts immune system. In topical uses, it relieves inflammation, insect bites, itching, irritation, rashes, and muscular aches and pains. Local wisdom revealed camphor oil for digestive problems treatment, bloating, relieve muscle and joint pain intensity. The compound 1.8 cineole has potential as antiviral, expectorant, and prospective for respiratory and blood vessels treatment.